Information needs and sources in everyday life information seeking of international postgraduate students - Utetleyeva, Zhazira (Nanyang Technological University, 2020)
Daily information seeking of international postgraduate students plays an important role in various stages of their life in a foreign country. Thus, the study aims to gain a deeper understanding of Everyday Life Information Seeking (ELIS) of international postgraduate students in Singapore through investigating the characteristics of their information needs, information sources, and main factors that may influence their daily information seeking. These aspects of ELIS have been studied through conducting 13 semi-structured interviews with international postgraduate students in Singapore. Depending on daily information seeking pattern, information needs have been divided into habitual and problem-specific information needs. Habitual needs included topics on personal interests and hobbies, and the news from the home country, host country, and other countries within participants’ interests. Problem-specific information needs are comprised of topics on travel, health, finance, housing, career, shopping, and legal matters. Known item inquiry and accidental information discovery practices have been associated with both categories of information needs. The primary information sources for international postgraduate students were web search engines, social contacts, social media, mass media, institutional sources, and university sources. Google and social media platforms were used extensively for different types of information needs, whereas social contacts were utilized selectively, mostly depending on the physical location of the human resource. Concerning university sources, students struggled to locate relevant and up-to-date information. Overall, both needs and sources were mainly under the influence of situational and individual factors. Regarding differences and similarities among international students, all students reported similar information needs and practices. However, students from China had more information resources to rely on compared to students from other countries. Another notable difference was that the language barrier provided obstacles to fulfilling the information needs of the students from China.